The implementation of Occupational Health and Safety (OHS) program on employee working conditions in the harvesting unit of PT Sewangi Sejati Luhur - Ferhat, Amallia; Nurdiansyah, Bayu; Suswatiningsih, Tri Endar; Bimantio, Mohammad Prasanto (OPSI, 2024)
PT. Sewangi Sejati Luhur, a palm oil plantation company, manages 7,000 hectares divided into 12 divisions across 3 estates. The company primarily focuses on cultivating and processing Fresh Fruit Bunches (FFB), with the harvesting unit employing the most workers. This research aims to investigate the implementation of the Occupational Health and Safety (OHS) program within the harvesting unit at PT Sewangi Sejati Luhur, designed to prevent work accidents and occupational diseases. Conducted in Tapung Hulu Subdistrict, Kampar Regency, Riau Province, the study employs a quantitative descriptive method using the HIRARC method to assess OHS application and employee working conditions. A saturated sample of 30 harvesting employees was surveyed through interviews and documentation of the OHS program. The findings reveal that the OHS program includes periodic health exams, OHS awareness campaigns, monthly activities, and training sessions. The program's implementation has led to low accident rates and satisfactory achievement of goals. Correlation analysis shows a significant link between OHS program implementation and improved employee working conditions. Additionally, 82% of respondents reported that the OHS program significantly influenced their working conditions, while 18% cited other factors. Overall, the OHS program in PT Sewangi Sejati Luhur's harvesting unit has been effective, ensuring a low accident rate and meeting monthly targets.